OPTIMIZATION BASED ON SATISFACTION WITH THE USE OF THE NATURAL MEDICINE INFORMATION SYSTEM (SI-OBAL) IN TRADITIONAL MEDICINE SERVICES AT SEMARANG HEALTH CENTER - Ratu, Modestus; Sequeira, Delita da Silva; Indrasari, Ferika; Asmani, Mohd Fadli Mohd; Siwi, Mayang Aditya Ayuning (jfpublisher, 2024)
Introduction. Public Health Efforts have been regulated in the Minister of Health Regulation on Health Centers, which is an activity carried out by health workers to maintain and improve health and to prevent disease aiming at families, groups and communities. In the context of these health efforts, activities are necessary for the utilization of natural medicines, by facilitating access to reliable information for the treatment of minor illnesses by health workers to be conveyed to the community. One of the works in the form of an application that helps pharmaceutical workers to obtain information on natural medicine quickly and precisely is called SI-OBAL (Sistem Informasi Bahan Alam/Natural Material Information System) web-based which can be used by pharmaceutical workers. The purpose of this research is to determine whether user satisfaction for optimal utilization of SI-OBAL in traditional medicine services at health centers in Semarang. Method. The method used was a prospective survey method with qualitative data measured by number and percentage. The population used was all pharmacy vocational staff working at the health center in Semarang. The method used to measure satisfaction is McLean and DeLone six parameters. Result & Analysis. The results of the research indicate that from the aspect of satisfaction measured, the results are 89.55% of pharmacy vocational staff are satisfied and very satisfied with having accessed SI-OBAL. Discussion. The optimization of health efforts in the community has significantly improved with the implementation of SI-OBAL in Traditional Medicine Services at the Semarang Health Center. This improvement indicates that the system effectively supports their pharmaceutical services, particularly in providing independent care using traditional medicine.